Head-synced Drone Control for Reducing Virtual Reality Sickness - Watanabe, Kandai; Takahashi, Masaki (Journal of Intelligent & Robotic Systems, 2020)
Controlling a drone using head-mounted display induces virtual reality (VR) sickness. From previous research, it is known that angular velocity is one of the contributing factors to induce VR sickness, however for drones, linear motion and the interaction between linear and angular motion often occur during operation. In this research, we investigate the effect of each conditions experimentally and proposes a method of controlling a drone to reduce VR sickness. We designed a system that does not make user’s head fixed at one point but allows to move the head freely. At the same time, the head orientation and direction are synced with the drone’s attitude to reduce sensory conflict. Two controllers were compared: joystick control and head control. We tested with a real system and conducted experiments on subjects to verify its effect. The proposed controller reduced angular velocity in the frequency range 0.1 to 10 Hz where a vestibular system becomes most sensitive, and it is demonstrated that reducing sensory conflict contributes to the reduction of VR sickness.